Epidemiological and faunistic characterization of scorpionism in the Beni Mellal-Khenifra region, Central Morocco. (30th October 2022) - Elmourid, Abdessamad; Elhidan, My Abdelmonaim; Boussaa, Samia; Bhiri, Mourad; Touloun, Oulaid
Abstract: Scorpionism is a serious public health problem in several parts of the world including Morocco, where is considered as the first cause of intoxication. The Beni Mellal-Khenifra region is one of the most affected regions by this health problem. The aim of this study is to describe the epidemiological and faunistic characteristics of scorpionism in this area. A retrospective epidemiological study was conducted based on the data of 16, 388 cases of scorpion stings recorded between 2016 and 2020. In the laboratory, the collected scorpions were determined morphologically based on the valid taxonomic keys. Statistical and descriptive analyses were performed using Excel 2016. Statistical significance was determined by P-value < 0.05. The study comprised 16, 388 stung patients. The scorpion stings incidence was 123.58 cases/100, 000 population/year and was significantly higher at Azilal province (217.69 cases/100, 000 population/year). We found a positive correlation between the scorpion stings incidence and the percentage of the rural population (r = 0.72) and between the scorpion stings incidence and the number of harmful species found in each province (r = 0.69). The general lethality rate was on average of 0.30% with a higher rate in Fquih Ben Salah province (0.63%) followed by Azilal province (0.32%). Children have the highest lethality than adults (p < 0.05). In the study area, eight species were identified, belonging to the families Buthidae and Scorpionidae, including dangerous species. Scorpionism is a real health problem in the Beni Mellal-Khenifra region, which is a rich and diverse area of scorpion fauna. Our findings can be useful for better understanding the problem of scorpionism in this region in order to better control it. Graphical abstract: Image 1 Highlights: The first study in the Beni Mellal-Khenifra region, central Morocco. A positive correlation between the scorpion stings incidence and the percentage of the rural population. Children have the highest lethality than adults. Eight species were identified, including dangerous species known by the high toxicity of their venoms.